(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
This study reports the synthesis and characterization of Fe(II), Cd(II), Hg(II) and Co(II) complexes with a Schiff base derived from lysine and salicylaldehyde. Elemental analysis confirmed successful synthesis. UV-Vis spectroscopy revealed significant electronic transitions and metal-to-ligand charge transfers. Thermogravimetric analysis showed distinct thermal decomposition patterns, indicating the stability and composition of the complexes. Magnetic susceptibility measurements indicated paramagnetic behavior for Fe(II) and Co(II) complexes, suggesting tetrahedral geometry, while Cd(II) and Hg(II) complexes were diamagnetic. X-ray diffraction analysis revealed a crystalline primitive lattice structure for the Fe(II) complex, with the Cd(II), Hg(II) and Co(II) complexes being amorphous. The Co(II), Cd(II) and Hg(II) complexes demonstrated substantial antibacterial activity against both gram-positive and gram-negative bacteria. Additionally, the Cd(II) and Co(II) complexes exhibited strong activity against all tested fungal strains. All complexes also showed promising antioxidant activity. Dhaka Univ. J. Pharm. Sci. 24(1): 29-37, 2025 (June)